TEACHER’S STRATEGIES IN TEACHING LISTENING COMRPEHENSION AT SMK BINA BERSAUDARA MEDAN - Nadiatul Hasanah; Rika Rika (Universitas Negeri Medan, 2021)
TEACHER’S STRATEGIES IN TEACHING LISTENING COMRPEHENSION AT SMK BINA BERSAUDARA MEDAN *Nadiatul Hasanah **Rika ABSTRACT Hasanah, Nadiatul. Registration Number: 2163321031. Teacher’s Teaching Strategies In Teaching Listening Comprehension At SMK Bina Bersaudara Medan. English Educational Program, Universitas Negeri Medan, 2020 This study aims to find out the teaching strategies implemented by teacher in teaching listening comprehension at SMK Bina Bersaudara Medan. The research was conducted by descriptive qualitative research through two phases: observing and interviewing. It was conducted in SMK Bina Bersaudara Medan at the XI grade class. The instruments of the research were: field notes and interview transcripts. The results of this research were first, there were only two strategies that applied by the teacher in teaching listening comprehension those are Metacognitive Strategies and Cognitive Strategies. The second was the underlying factor of using those kinds of strategies in teaching listening comprehension namely the effectiveness of teachers in teaching, basically a teacher should be a good communicator, should teach the students effectively and many more which makes a teacher become professional and the most important part is the instruction strategies which she chooses to deliver the materials which helps students in learning more effective. Key words :Teacher’s Strategies, Listening Comprehension, Teaching Listening